Tiger eyes - Blume, Lawrence, (Director); Blume, Judy; Blume, Judy; Holland, Willa, 1991-; Johnson, Amy Jo; Stevenson, Cynthia, 1962-; Means, Tatanka; Larson, Nathan, 1970-; Tashmoo Productions; Amber Entertainment; Freestyle Digital Media (Los Angeles, CA : Distributed by Freestyle Digital Media, 2014)
Davey is a 17 year-old girl abruptly relocated by her grieving mother to the strange 'atom bomb' town of Los Alamos, New Mexico. With the sudden and violent death of her father, the displaced Davey no longer knows who to be or how to fit in. Everything that once mattered suddenly seems insignificant. But when she meets Wolf, a mysterious young Native-American, while exploring the surrounding canyons, she feels he is able to see past her pain and into her true self.
Based on the novel by Judy Blume.
Originally released as a motion picture in 2012.
Special features: audio commentary by author Judy Blume and director Lawrence Blume; theatrical trailer.
Editor, Jay Freunddirector of photography, Seamus Tierney ; music, Nathan Larson.
Willa Holland, Amy Jo Johnson, Cynthia Stevenson, Tatanka Means, Russell Means.
MPAA rating: PG-13.
Keywords: Blume, Judy -- Film and video adaptations; Fathers -- Death -- Drama; Bereavement in adolescence -- Drama; Grief -- Drama; Anger -- Drama; Families -- Drama; Death -- Drama; Los Alamos (N.M.) -- Drama; Atlantic City (N.J.) -- Drama; New Mexico -- Drama; New Jersey -- Drama; Feature films; Video (DVD); Based on the book